Relationship of Nitrogen Use Efficiency with the Activities of Enzymes Involved in Nitrogen Uptake and Assimilation of Finger Millet Genotypes Grown under Different Nitrogen Inputs - Nidhi Gupta; Atul K. Gupta; Vikram S. Gaur; Anil Kumar (The Scientific World Journal)
Nitrogen responsiveness of three-finger millet genotypes (differing in their seed coat colour) PRM-1 (brown), PRM-701 (golden), and PRM-801 (white) grown under different nitrogen doses was determined by analyzing the growth, yield parameters and activities of nitrate reductase (NR), glutamine synthetase (GS), glutamate synthase; GOGAT, and glutamate dehydrogenase (GDH) at different developmental stages. High nitrogen use efficiency and nitrogen utilization efficiency were observed in PRM-1 genotype, whereas high nitrogen uptake efficiency was observed in PRM-801 genotype. At grain filling nitrogen uptake efficiency in PRM-1 negatively correlated with NR, GS, GOGAT activities whereas it was positively correlated in PRM-701 and PRM-801, however, GDH showed a negative correlation. Growth and yield parameters indicated that PRM-1 responds well at high nitrogen conditions while PRM-701 and PRM-801 respond well at normal and low nitrogen conditions respectively. The study indicates that PRM-1 is high nitrogen responsive and has high nitrogen use efficiency, whereas golden PRM-701 and white PRM-801 are low nitrogen responsive genotypes and have low nitrogen use efficiency. However, the crude grain protein content was higher in PRM-801 genotype followed by PRM-701 and PRM-1, indicating negative correlation of nitrogen use efficiency with source to sink relationship in terms of seed protein content.